2019
DOI: 10.1021/acscatal.9b00482
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostannation of Alkynes

Abstract: In this review, we present an overview of hydrostannation of alkynes until the end of 2018. Mechanism of the tin hydride addition on a triple bond is discussed at the beginning of this review in the presence of metal catalysts as Pd, Ru-based complexes, Lewis acids and under radical conditions. Then, stereoselectivity as well as regioselectivity aspects of tin hydride addition on the carbon triple bond is discussed using metal-catalysis, radical conditions or Lewis acids. In each of these items, the reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 222 publications
0
52
0
Order By: Relevance
“…Thus, the treatment of 1 a and 2 with Zn(OTf) 2 (Tf=SO 2 CF 3 ; 5 mol%) and pyridine (10 mol%) in EtCN at 70 °C for 8 h provided tributyl(phenylethynyl)tin ( 3 a ) in 20% yield, but with a considerable amount of undesired hydrostannylation products 4 a as an E / Z mixture (72:28). Radical‐induced hydrostannylation of 1 a with 2 has been reported to predominantly yield E ‐ 4 a , implying that the E ‐enrichment in Scheme is likely to be due to the involvement of a radical species. To confirm this conjecture and also to reduce the radical influence, the reaction was conducted in the presence of 2,2,6,6‐tetramethylpiperidine 1‐oxyl (TEMPO; 50 mol%) known as a radical scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the treatment of 1 a and 2 with Zn(OTf) 2 (Tf=SO 2 CF 3 ; 5 mol%) and pyridine (10 mol%) in EtCN at 70 °C for 8 h provided tributyl(phenylethynyl)tin ( 3 a ) in 20% yield, but with a considerable amount of undesired hydrostannylation products 4 a as an E / Z mixture (72:28). Radical‐induced hydrostannylation of 1 a with 2 has been reported to predominantly yield E ‐ 4 a , implying that the E ‐enrichment in Scheme is likely to be due to the involvement of a radical species. To confirm this conjecture and also to reduce the radical influence, the reaction was conducted in the presence of 2,2,6,6‐tetramethylpiperidine 1‐oxyl (TEMPO; 50 mol%) known as a radical scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent mechanistic studies into "classical" reactions involving tin hydrides have revealed fascinating complexity and paved the way to rational development of improved reaction protocols. [14][15][16][17][18][19] The addition of antimony hydrides (primary or secondary stibines) to multiple bondshydrostibination -has been explored to a very limited extent, 20, 21 with well-defined examples being restricted to cases that proceed under Lewis-acid or radical-initiator (azobisisobutyronitrile, AIBN) mediated conditions. 22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…Now, despite the electronically-controlled stannylvinyl cationic ion pair hypothesis 5 of Scheme 3 (mechanism 3) conflicting very strongly with the 2005 radical probe work of Scheme 2, 1,3 and Alabugin's later 2015 experimental work and DFT calculations, 4 which further confirmed an entirely free radical O-directed mechanism for these reactions (mechanism 1), still mechanism 3 5 remains active and unwithdrawn from the literature, despite several criticisms, 1,4,6 with the consequence that its mechanistic principles are still continuing to be widely disseminated within the community. This is best illustrated by a recent 2019 hydrostannation review, 7 where exclusivity of discussion and mechanistic primacy were given to mechanism 3 over mechanism 1 to explain the conversion of 11 into (Z)-15. However, as we have seen, mechanism 3 5 is at great odds with all experimental data gathered to date.…”
Section: Methodsmentioning
confidence: 99%